2015
DOI: 10.7448/ias.18.6.20285
|View full text |Cite
|
Sign up to set email alerts
|

“Violence. Enough already”: findings from a global participatory survey among women living with HIV

Abstract: IntroductionWomen living with HIV are vulnerable to gender-based violence (GBV) before and after diagnosis, in multiple settings. This study's aim was to explore how GBV is experienced by women living with HIV, how this affects women's sexual and reproductive health (SRH) and human rights (HR), and the implications for policymakers.MethodsA community-based, participatory, user-led, mixed-methods study was conducted, with women living with HIV from key affected populations. Simple descriptive frequencies were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 21 publications
6
46
0
Order By: Relevance
“…Gender‐based violence (GBV) disproportionately impacts and compromises the wellbeing of women and girls across the world . A global participatory survey among women living with HIV (WLHIV) found that 89% of those who responded to the GBV section reported having experienced or feared GBV . GBV has deleterious impacts on physical and mental health .…”
Section: Introductionmentioning
confidence: 99%
“…Gender‐based violence (GBV) disproportionately impacts and compromises the wellbeing of women and girls across the world . A global participatory survey among women living with HIV (WLHIV) found that 89% of those who responded to the GBV section reported having experienced or feared GBV . GBV has deleterious impacts on physical and mental health .…”
Section: Introductionmentioning
confidence: 99%
“…However, many people living with HIV, particularly women, may be hesitant to disclose their HIV status due to fear of stigma, discrimination and particularly violence [36,37]. To reduce the risk of violence resulting from HIV status disclosure to a partner, HIV and SRHR policymakers, programme managers and healthcare providers could work towards developing and implementing novel approaches for safer disclosure, including assessing for partner violence and engaging peer-counsellors and communities of people living with HIV [38][39][40]. There is also a need to explore programmatic and clinical approaches that could be used in cases of nondisclosure of HIV status when disclosure could increase harm [41].…”
Section: Facilitated Disclosure Of Hiv Statusmentioning
confidence: 99%
“…The right to sexual and reproductive health services (SRHS) is understood as the possibility of having easy access to and receiving timely and efficient care that meets the needs of women throughout their life course as well as the freedom to make reproductive decisions. However, studies regarding women living with HIV (WLHIV) and their conditions for accessing SRHS show that their SRH needs are largely unmet , leading to high rates of unsafe abortions and three times the number of unplanned pregnancies than women not living with HIV (WNLHIV) . In 2017, the World Health Organization (WHO) launched the Consolidated Guideline on Sexual and Reproductive Health and Rights of Women Living with HIV to support countries to implement evidence‐based interventions to improve access to SRHS and contribute to the realization of this basic right .…”
Section: Introductionmentioning
confidence: 99%